Perbedaan Efektivitas Penggunaan Media Video dan E-Book terhadap Pengetahuan Fisiologi Menstruasi Mahasiswa Kebidanan - Verawati Pulungan; Ry Eny Mian Marisi Br Simanjuntak; Rice Silvanora (Jurnal Akademika Baiturrahim Jambi, 2026)
Knowledge of menstrual physiology is crucial for midwifery students. Menstrual physiology encompasses vital information regarding ovulation periods, fertile windows, and related hormones. A lack of understanding can lead to inaccuracies in providing patient education and risks reinforcing misconceptions about menstruation. Technology-based learning media, such as animated videos and e-books, are options to enhance student knowledge. This study aims to determine the effectiveness of video and e-book learning media on knowledge of menstrual physiology among Applied Bachelor of Midwifery students. This research employed a quasi-experimental two-group pretest-posttest design. The study was conducted at the Department of Midwifery, Poltekkes Kemenkes Jambi. The population consisted of 60 fifth-semester midwifery students. Using a total sampling technique, 60 participants were divided into two groups: the odd-numbered attendance group (30 students) as the Video group and the even-numbered attendance group (30 students) as the E-book group. The results indicated that both video and e-book media significantly influenced the increase in student knowledge, with a p-value of 0.001<0.05. Regarding the comparison of effectiveness between the two, the mean difference was 1.10 with a p-value of 0.12>0.05, indicating no significant difference between the two media. Both video and e-book media are effective for use as learning tools. The selection and utilization of these media should be tailored to the learning preferences and needs of the students.